(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This article analyzes the presence of legal norms regulating insurance relations in regulatory documents of various fields (constitutional, administrative, environmental and other branches of law). It is analyzed that the set of regulatory documents containing insurance standards forms a complex, cross-sectoral legislation on insurance, and that civil legal sources of insurance law form a certain system, in which the Civil Code of the Republic of Uzbekistan and the Law "On Insurance Activities" occupy a central place.